Assessment of Subjective Sleep Problems in Men With Opioid Dependence Maintained on Buprenorphine. Issue 2 (March 2020) - Tripathi, Richa; Dhawan, Anju; Rao, Ravindra; Mishra, Ashwani Kumar; Jain, Raka; Sinha, Sanjeev
Abstract : Objectives: To assess the rates of sleep disturbances in male patients with opioid dependence maintained on buprenorphine and to assess the factors associated with sleep disturbances in this population. Methods: Observational, cross-sectional study. Male patients with opioid dependence aged 18 years and older, and started on buprenorphine at least 6 months before were screened. Those with history of comorbid psychiatric illnesses (except sleep disorders), on any other substance in high-risk category (based on WHO-Alcohol Smoking Substance Involvement Screening Test (ASSIST)), or on any other psychotropic medications (in addition to OAT with buprenorphine) were excluded. Sleep was assessed using the Pittsburgh Sleep Quality Index (PSQI), Sleep-50, and Epworth Sleepiness Scale (ESS). Each participant was interviewed in a single session lasting 60 minutes. Results: One hundred six participants were included. Their mean age was 41.1 (SD 14.3) years. The participants had been on OAT with buprenorphine for a median duration of 60 months (IQR 17–120), with excellent adherence rate in past 1 month. The mean current dose of buprenorphine was 10.2 (SD 3.8) mg per day. The mean subjective total sleep time was 403.5 minutes (SD 94.8) and the median sleep latency was 35 minutes (IQR 18.8–62.5). The mean PSQI score was 6.6 (SD 3.4). Nearly 63% (n = 67) participants had PSQI scores more than 5 (PSQI > 5) suggesting sleep problems. Sociodemographic, substance use, and treatment variables were compared between participants who scored more than 5 and those who scored less than 5 on PSQI. No significant difference was found between the 2 groups. Conclusions: Substantial proportion of male patients with opioid dependence maintained on buprenorphine have sleep problems. The sleep problems in buprenorphine-maintained patients seem to be independent of substance use and treatment-related attributes.